A characterization of the cardiac physiology and aortic pulse wave properties of artistic swimmers across competitive levels - Baker, R. E.; Cheung, C. P.; Coates, A. M.; Currie, K. D.; King, T. J.; Mountjoy, M. L.; Burr, J. F. (Medicine & Science in Sports & Exercise, 2024)
Purpose The distinct physical and environmental stressors of artistic swimming (previously termed synchronized swimming) result in unique hemodynamic stimuli. Given that the hemodynamic stress associated with participation in an exercise modality drives adaptation of the heart and central vasculature, artistic swimming may produce a distinct cardiovascular phenotype. Presumably, athletes competing at the highest levels also have greater training exposure and thus exhibit more adaptation. The purpose of this study was to characterize cardiovascular form and function across the competitive spectrum of artistic swimmers.